Optimalisasi Produksi Alat Angkut Dump Truck Scania Patria x pro Model tv45 Berdasarkan Analisis Masalah Fishbone Pada Aktivitas Penambangan Batubara di seam A site Rantau PT. Kalimantan Prima Persada, Kecamatan Tapin Utara, Kabupaten Tapin, Provinsi Kalimantan Selatan. - Ikhwan Pratama; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The process of loading and transporting coal at PT. Kalimantan Prima Persada from the front to the crusher using a combination of 1 PC 400 type excavator with a capacity of 3.2 Lcm and a heavy tipper scania patria x pro model tv45 dump truck with a vessel capacity of 39 tons with 7 units of tools. In 1 month the planned production target is 163,054.23 tons / month.This study uses the QCC method to increase coal production targets. In the actual achievement in the field before the increase in production, only 121,314.78 tons / month were achieved or 74.40% of the target set by the company. Based on the paretto analysis, the main problem of not achieving coal production is the amount of work time wasted 2,277.78 hours / month from the available time of 5040 hours / month.By making improvements to wasted working time using the QCC method for coal production of PT. Kalimantan Prima Persada increased to 39%. Keywords: Excavator, Dumptruck, Production, Quality Control Circle, Paretto.